Analysis of Strengths of Reinforced Concrete Beam Structures with CFRP Sheet Using Abaqus Software 6.14 - Yasir, Ahmad; Effendi, Mahmud Kori; Taveriyanto, Arie; Apriyatno, Henry (Semarang State University, 2019)
Abstract. Concrete beams are parts of a structure that serves as a channeling moment to the column structure. The structure of the beam which has undergone yielding reinforcement must be repaired. One of the beam repairs that can be done is by providing reinforcement using Carbon Fiber Reinforced Polymer (CFRP) sheets. The reinforcement structure modeling and analysis were carried out using the Abaqus software. There are two types of modeling, those were laboratory test beam modeled with Abaqus (BPA) and reinforced beam using CFRP (BPC). The beam structure analysis using Abaqus software showed that BPA beam experiences a first crack when the load is 5311.96 lbs with a 0.08 inch displacement, while the BPC-2 beam is first cracked at a load of 5019.93 lbs with a 0.10 inch displacement. The BPA beam experiences an ultimate when the load was 12620.84 lbs with a 0.64-inch displacement, while the BPC-2 beam experiences ultimate when the load was 12403.48 lbs with a displacement of 0.60 inch. The type of crack pattern in both beam models is the type of bending crack.